Parental reports of serious illness and disability among children aged 3–16 years from UK military families - Khera, C; Stevelink, S; Fear, N (BMJ Publishing Group, 2016)
Prevalence rates of child illness according to parents have been found to vary greatly in the general population, with even less known about children of military parents. Mothers are generally considered more informed about their children's problems than fathers. This paper aimed to establish the prevalence of serious illness and disability among children from military families, noting the difference between parental reports.Male serving and ex-serving personnel with children aged 3-16 years were invited to take part in an online questionnaire and telephone interview based on their child's health. The mothers of their children were invited via post if the father gave permission to make contact. Data were analysed using descriptive statistics and Cohen's kappa.378 fathers and 383 mothers provided information for 610 children. The vast majority of parents did not perceive their child to have a serious illness or disability; fathers reported problems in 7.7% of their children (respiratory conditions most common), while mothers reported problems in 6.2% (physical health problems rated most prevalent). A moderate agreement was found between parent's reports; kappa=0.51 (p<0.001).The prevalence of serious illnesses and disabilities is low among military children according to parent reports. Fathers were more likely to disclose a problem in their child, and these differences were visible in the type of problem reported also. This disparity suggests mothers' and fathers' views should both be considered when making decisions that involve the child's care, in addition to clinical diagnoses.